Trajectories of mental health among UK university staff and postgraduate students during the pandemic. Issue 8 (20th March 2022) - Carr, Ewan; Oetzmann, Carolin; Davis, Katrina; Bergin-Cartwright, Gabriella; Dorrington, Sarah; Lavelle, Grace; Leightley, Daniel; Polling, Catherine; Stevelink, Sharon A M; Wickersham, Alice; Vitiello, Valentina; Razavi, Reza; et al.
Abstract : Objectives: The COVID-19 pandemic has disrupted the social and working lives of many. Past studies have highlighted worsening mental health during the pandemic, but often rely on small samples or infrequent follow-up. This study draws on fortnightly assessments from a large occupational cohort to describe differing trajectories of mental health between April 2020 and April 2021 and individual characteristics associated with these trajectory types. Methods: King's College London Coronavirus Health and Experiences of Colleagues at King's is an occupational cohort study at a large university in London, UK. Participants (n=2241) completed online questionnaires fortnightly between April 2020 and April 2021. Symptoms of anxiety and depression were assessed using Generalised Anxiety Disorder (GAD-7) and Patient Health Questionnaire (PHQ-9). Results: On average, participants reported low levels of anxiety and depression (GAD-7 and PHQ-9 scores of 0–9, consistent with 'none', 'minimal' or 'mild' symptoms) throughout the year, with symptoms highest in April 2020 and decreasing over the summer months when no lockdown measures were in place. However, we observed more severe and variable symptoms among subgroups of participants. Four trajectory types for anxiety and depression were identified: 'persistent high severity' (6%–7% of participants), 'varying symptoms, opposing national cases' (4%–8%), 'varying symptoms, consistent with national cases' (6%–11%) and 'persistent low severity' (74%–84%). Younger age, female gender, caring responsibilities and shielding were associated with higher severity trajectory types. Conclusions: These data highlight differing individual responses to the pandemic and underscore the need to consider individual circumstances when assessing and treating mental health. Aggregate trends in anxiety and depression may hide greater variation and symptom severity among subgroups.